EVALUASI TERHADAP KUALITAS LULUSAN MAGISTER ILMU HUKUM AKIBAT KEBIJAKAN PENERIMAAN PESERTA DIDIK NON SARJANA HUKUM - Roestamy, Martin (Jurnal Sosial Humaniora, 2021)
In the last two decades there has been a paradigm shift where for masters of law can be from non-law graduates, so that the postgraduate education system of law school will have multidisciplinary students input. On the other hand, students who are not from legal studies have limited knowledge of legal principles, theories, concepts, ways of thinking, and do not even know the laws and regulations as the basis for legal research. In particular, normative juridical research requires sharp intuition of the law, which unfortunately for non-law students conducts research that mostly does not touch the substance of the philosophy of legal study. The research questions posed in this paper are: How to improve the quality of Law Graduate Program students with non-law backgrounds? This paper aims to provide solutions to obstacles in quality and effective postgraduate law education both in society and for the development of legal science itself. Furthermore, it is concluded that it is not easy to transform the nature of legal science to non-law students who enter legal education, given the weak understanding of principles, rules, institutions and legal processes. Thus, it is recommended from this study that: 1). Graduates with non-law backgrounds may not be leaders in drafting laws and regulations, especially those working in any government agency, and 2). Postgraduate Law must rearrange the curriculum for students who are not graduates of Law, for example by providing basic matriculation of law within two semesters or stopping multidisciplinary programs altogether.